Vegetative and generative growth of groundnut genotypes under biotic environmental stress (Biodiversitas Journal of Biological Diversity, 2016)
Rahmianna AA, Yusnawan E. 2016. Vegetative and generative growth of groundnut genotypes under biotic environmental stress. Biodiversitas 17: 503-509. The decrease in groundnut pod yield is mainly influenced by disease infestation, especially bacterial wilt and foliar diseases. The objectives of this experiment were to determine the response and tolerance of groundnut genotypes to bacterial wilt, leaf spot and rust diseases, and seed infection by Aspergillus flavus. The planting materials were 25 genotypes (11 Indonesian cultivars, 12 lines introduced from ICRISAT, 1 Indonesian promising line, and 1 local cultivar) with various superiorities on diseases resistance. This study was arranged in a randomized completely block design with triplicate. The results indicated that both genotypes from ICRISAT and Indonesia had similar response to leaf spot i.e. ranging from susceptible (score 6-7) to highly susceptible (8-9). The score for rust ranged from moderately resistant to susceptible. The average pod yield was 23.1 g/plant (from 11.9 g to 29.5 g), and 13 and 12 genotypes produced pods higher and lower than the average value, respectively. ICGV 86158 and ICGV 95322 had the highest and lowest seeds as well as pod productivity, respectively. The ICRISAT genotypes were susceptible to Ralstonia solanacearum infection, except for ICGV 86590. Among the Indonesian cultivars, those with Valencia type of growth, relatively had better resistance to bacterial infection. These cultivars were also resistant to rust and A. flavus infection.
Keywords: Biotic stress, generative, groundnut, vegetative performance